Method for improving performance of asphalt pavement by compounding gradient fiber mixing amount with gradient high modulus agent mixing amount
By adding gradient high-modulus agent and graded fibers to different levels of the asphalt pavement structure, the problem of poor flexibility of high-modulus asphalt mixture at low temperatures is solved, and the efficient rut resistance and crack resistance of asphalt pavement is achieved. Extend the service life of the road surface.
Patent Information
- Application Number
- CN202411404169.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-14
AI Technical Summary
High-modulus asphalt mixtures have poor flexibility at low temperatures, which are prone to cracking, making them difficult to promote and apply on a large scale in cold areas.
By adding gradient high-modulus agents and graded fibers to different levels of the asphalt pavement structure, the gradient graded fiber doping and gradient high-modulus agent doping are formed to improve the rut resistance and crack resistance of the asphalt pavement.
On the basis of improving the dynamic modulus of the asphalt pavement structure, it greatly enhances its deformation resistance and low-temperature crack resistance, reduces ruts and cracks, and extends the service life of the pavement.
Smart Images

Figure CN119434049A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of asphalt pavement structure, and in particular relates to a method for improving asphalt pavement performance by compounding a gradient fiber dosage with a gradient high modulus agent dosage. Background Art
[0002] High modulus asphalt mixture is widely used in heavy-load traffic sections due to its excellent high-temperature anti-rutting performance and mechanical properties. High modulus asphalt mixture reduces the compressive stress and compressive strain of the asphalt pavement structure under traffic load by increasing the modulus of the asphalt mixture (which can reach an average of 15000-20800Mpa (20℃, 10Hz)), thereby enhancing its anti-deformation ability. In the high-temperature performance test, the dynamic stability, rutting depth and permanent deformation indicators obtained by different test methods all confirmed that the high modulus asphalt mixture has good anti-rutting performance.
[0003] However, high modulus asphalt mixtures have poor flexibility and are prone to cracking at low temperatures, making them difficult to be widely used in cold regions. Fiber, as an additive, can be added to asphalt mixtures to not only improve their high temperature performance and low temperature crack resistance, but also improve the elastic modulus and uniformity of force distribution, while reducing reflective cracks in asphalt mixtures and pavement, and extending the service life of asphalt pavement. Among them, basalt fiber has excellent mechanical properties, and the overlapping fiber network in the mixture can constrain the expansion of microcracks, thereby improving the crack resistance of the mixture.
[0004] Based on this, a method of improving the performance of asphalt pavement by combining gradient fiber dosage with gradient high modulus agent dosage is studied, which can improve the anti-rutting performance of asphalt pavement and the anti-cracking performance at the same time. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for simultaneously improving the rutting resistance and cracking resistance of asphalt pavement by compounding a gradient fiber dosage with a gradient high modulus agent dosage.
[0006] Technical solution: The method of improving the performance of asphalt pavement by compounding the gradient fiber dosage with the gradient high modulus agent dosage of the present invention comprises the following steps:
[0007] (1) Providing an asphalt pavement structure including an asphalt upper layer, an asphalt middle layer, an asphalt lower layer, a base layer and a subbase layer;
[0008] (2) Add 0.8-1.0% of high modulus agent and 0.3-0.4% of graded fiber to the asphalt mixture of the upper asphalt layer; add 0.8-1.0% of high modulus agent and 0.3-0.4% of graded fiber to the asphalt mixture of the middle asphalt layer; add 0.3-0.5% of high modulus agent and 0.3-0.4% of graded fiber to the asphalt mixture of the lower asphalt layer, so as to form a gradient graded fiber dosage and a gradient high modulus agent dosage.
[0009] The present invention forms a gradient incorporation method by compounding high modulus agents and graded fibers on different pavement layers, thereby greatly enhancing the deformation resistance and low-temperature crack resistance of the asphalt pavement structure on the basis of improving the dynamic modulus, thereby reducing rutting and cracks on the asphalt pavement and extending the service life of the pavement.
[0010] Specifically, the present invention, by compounding high modulus agents on different pavement layers and forming a gradient addition method, on the one hand, improves the modulus of asphalt mixtures of different pavement layers by taking into account the differences in asphalt dosage of different asphalt mixtures; on the other hand, by taking into account the shear stress distribution characteristics within the asphalt pavement of different pavement layers, the dosage of high modulus agent in the asphalt middle layer is increased to improve the shear strength of the asphalt mixture of the middle layer, thereby improving the rutting resistance of the overall pavement structure formed.
[0011] At the same time, adding fibers to high modulus asphalt mixtures and adding them in a graded fiber and shape gradient manner according to the mineral gap characteristics and low-temperature cracking performance of different asphalt mixtures can not only improve the low-temperature crack resistance of each layer of the mixture, but also improve the crack resistance of the overall pavement structure.
[0012] Furthermore, in step (2) of the method for improving the performance of asphalt pavement of the present invention, the design ratio of the graded fibers is:
[0013] M 3n mm :M 3(n-1)mm :┄┄:M3 mm =[Xm 3n mm *X 3n mm (0°~45°)+Ym 3n mm *Y 3n mm
[0014] (45°~90°)]:[Xm 3(n-1)mm *X 3(n-1)mm (0°~45°)+Ym 3(n-1) *Y 3(n-1)mm (45°~90°)]:┄┄:[Xm 3mm *X3mm (0°~45°)+Ym3 mm *Y 3mm (45°~90°)];
[0015] Where M 3nmm is the mass ratio of 3nm fiber; Xm 3nmm is the mass ratio of fibers of different lengths in the transverse section; X 3nmm (0-45°) is the guide coefficient ratio of fibers of different lengths with an angle between 0° and 45° with the transverse section; Y 3nmm Ym is the mass ratio of fibers of different lengths in the longitudinal section; 3nmm (45°~90°) is the ratio of the guidance coefficients of fibers of different lengths whose angles with the longitudinal section are between 45° and 90°; n is a positive integer.
[0016] Furthermore, the design method of the graded fiber of the present invention comprises the following steps:
[0017] (1) According to the gradation and asphalt-stone ratio of asphalt mixture, cylindrical specimens and rectangular specimens without fibers were prepared respectively;
[0018] (2) According to the gradation, asphalt-stone ratio and fiber volume content of the asphalt mixture, 3n mm single fiber cylindrical specimens were prepared, where n is a positive integer;
[0019] (3) respectively obtaining skeleton feature images of different horizontal layers of the cylindrical specimen and skeleton feature images of different vertical layers of the rectangular specimen in step (1), and respectively performing binary image processing on both, so as to distinguish the skeleton and the gap between the skeletons of the asphalt mixture, and obtain binary images of the horizontal and vertical surfaces;
[0020] (4) Based on the binary images of the transverse and longitudinal surfaces, the skeleton gap features of the binary images of the asphalt mixture are extracted, and the length data of the skeleton gaps are arranged in intervals to count the number of different intervals [3n-3,3n) mm and determine the lengths of different Xm 3nmm and Ym 3nmm The relative mass ratio of the length fiber; where X represents the transverse section, Y represents the longitudinal section, n is a positive integer, and m is the mass;
[0021] (5) Obtain cross-sectional images of cylindrical specimens with single fibers of different lengths in step (2) respectively, obtain dispersion effect extraction diagrams of single-length fibers in asphalt mixtures, calculate fiber angles, and calculate the guide coefficient ratios of single-length fibers with angles between 0° and 45° and 45° and 90° with the bottom cross-plane, which are defined as X 3nmm (0~45°), Y 3nmm(45°~90°), X represents the transverse section, and Y represents the longitudinal section;
[0022] (6) Combine the different Xm in step (4) 3nmm and Ym 3nmm The relative proportion of the length fibers and the guide coefficient ratio of the single length fibers in step (5) determine the final design ratio of the length fibers based on the three-dimensional feature combination:
[0023] M 3n mm :M 3(n-1)mm :┄┄:M 3 mm =[Xm 3n mm *X 3n mm (0°~45°)+Ym 3n mm *Y 3n mm (45°~90°)]:[Xm 3(n-1)mm *X 3(n-1)mm (0°~45°)+Ym 3(n-1) *Y 3(n-1)mm (45°~90°)]:┄┄:[Xm 3mm *X 3mm (0°~45°)+Ym 3mm *Y 3mm (45°~90°)]; where M 3nmm is the mass ratio of 3n mm fiber.
[0024] The fiber dosage gradation design method of the present invention can form a real "three-dimensional network" structure by overlapping fibers of different lengths in the mixture, thereby maximizing the enhancement of the asphalt pavement performance formed by the method.
[0025] Furthermore, in step (3) of the method for designing graded fibers of the present invention, the binarization image processing is performed based on MATLAB software to achieve the distinction between the skeleton and the gap between the skeletons.
[0026] Furthermore, in step (4) of the method for designing graded fibers of the present invention, the extracted characteristic parameter is the principal axis length of the skeleton gap in the binary image.
[0027] Preferably, further, in step (4) of the design method for graded fibers of the present invention, the value of n is 1≦n≦4, and the corresponding distribution interval of the length data of the skeleton gap is (0,3), [3,6), [6,9), [9,12]. Based on the value of n, the relative proportions of the combined length fibers determined in the transverse and longitudinal planes are Xm and Xm, respectively. 3mm :Xm 6mm :Xm 9mm :Xm 12mm and Ym 3mm :Ym 6mm:Ym 9mm :Ym 12mm The design ratio of the three-dimensional characteristic combined length fiber is:
[0028] M 3mm :M 6mm :M 9mm :M 12mm =[Xm 3mm *X 3mm (0°~45°)+Ym 3m *Y 3mm (45°~90°)]:[Xm 6mm *X 6mm (0°~45°)+Ym 6mm *Y 6mm (45°~90°)]:[Xm 9mm *X 9mm (0°~45°)+Ym 9mm *Y 9mm (45°~90°)]:[Xm 12mm *X 12mm (0°~45°)+Ym 12mm *Y 12mm (45°~90°)].
[0029] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are: this method, by compounding high modulus agents and graded fibers on different pavement layers and forming a gradient incorporation method, can greatly enhance its anti-deformation ability and low-temperature crack resistance on the basis of improving the dynamic modulus of the asphalt pavement structure, so as to reduce rutting and cracks on the asphalt pavement, thereby extending the service life of the pavement. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a binary image of a certain transverse cross section of the upper layer SMA-13 asphalt concrete specimen of the present invention; wherein, a is the original image of a certain transverse cross section; b is the image enhancement grayscale image; c is the denoised image; and d is the binary image. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0032] The method of improving the performance of asphalt pavement by compounding a gradient fiber dosage with a gradient high modulus agent dosage of the present invention comprises the following steps:
[0033] (1) Providing an asphalt pavement structure including an asphalt upper layer, an asphalt middle layer, an asphalt lower layer, a base layer and a subbase layer;
[0034] (2) Add 0.8-1.0% of high modulus agent and 0.3-0.4% of graded fiber to the asphalt mixture of the upper asphalt layer; add 0.8-1.0% of high modulus agent and 0.3-0.4% of graded fiber to the asphalt mixture of the middle asphalt layer; add 0.3-0.5% of high modulus agent and 0.3-0.4% of graded fiber to the asphalt mixture of the lower asphalt layer, so as to form a gradient graded fiber dosage and a gradient high modulus agent dosage.
[0035] The specific asphalt concrete used in the asphalt upper layer, asphalt middle layer and asphalt lower layer of the present invention can be adaptively adjusted according to the actual road section, pavement structure and application environment, and can be prepared according to the requirements of "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004) and "Highway Engineering Asphalt and Asphalt Mixture Test Procedure" (JTG E20-2011). For example, the upper layer is prepared into a pavement structure using SMA-13 asphalt concrete, the middle layer is prepared into a pavement structure using AC-20 medium-grained asphalt concrete, and the lower layer is prepared into a pavement structure using AC-25 coarse-grained asphalt concrete. The design method of the present invention, that is, the high modulus agent and graded fiber are compounded on different pavement layers to form a gradient, can greatly enhance the deformation resistance and low-temperature crack resistance of the asphalt pavement structure on the basis of improving the dynamic modulus of the asphalt pavement structure, so as to reduce rutting and cracks on the asphalt pavement, thereby extending the service life of the pavement.
[0036] In addition, the high modulus agent defined in the present invention is a high modulus agent well known in the art, such as a polyolefin high modulus agent.
[0037] That is, the present invention does not impose any restrictions on the specific materials used for the asphalt upper layer, asphalt middle layer, asphalt lower layer, base layer, subbase layer and high modulus agent, and can be flexibly arranged according to actual needs.
[0038] Example 1
[0039] The method of improving the performance of asphalt pavement by compounding the gradient fiber dosage with the gradient high modulus agent dosage in Example 1 comprises the following steps:
[0040] (1) An asphalt pavement structure is provided, including a 4 cm SMA-13 asphalt concrete upper layer with an oil-to-stone ratio of 6.0%, a 6 cm AC-20 medium-grained asphalt concrete asphalt middle layer with an oil-to-stone ratio of 4.8%, an 8 cm AC-25 coarse-grained asphalt concrete asphalt lower layer with an oil-to-stone ratio of 4.3%, a 36 cm cement-stabilized crushed stone base with a cement dosage of 5%, and an 18 cm low-dose cement-stabilized crushed stone subbase with a cement dosage of 4%. The specific gradation composition of the cement-stabilized crushed stone base and the low-dose cement-stabilized crushed stone subbase is determined by the recommended gradation range in the "Technical Specifications for Construction of Highway Pavement Base" (JTG F20-2015). The gradation composition of the cement-stabilized crushed stone base and the low-dose cement-stabilized crushed stone subbase in this embodiment is shown in Table 1 below;
[0041] Table 1 Gradation composition of cement stabilized gravel and low-dose cement stabilized gravel
[0042]
[0043] (2) 1.0% of the total amount of high modulus agent and 0.3% of the total amount of graded fiber are added to the asphalt concrete of the asphalt upper layer; 1.0% of the total amount of high modulus agent and 0.35% of the total amount of graded fiber are added to the asphalt mixture of the asphalt middle layer; 0.4% of the total amount of high modulus agent and 0.4% of the total amount of graded fiber are added to the asphalt mixture of the asphalt lower layer, forming a gradient graded fiber dosage and a gradient high modulus agent dosage;
[0044] Among them, for the asphalt concrete top layer of 4cm SMA-13 and 6.0% asphalt aggregate ratio, the fiber grading design method includes the following steps:
[0045] (1) Based on the asphalt concrete with 4 cm SMA-13 and an asphalt-stone ratio of 6.0%, a rotary compaction specimen with a diameter of 150 mm and a height of 170 mm (excluding fiber) was formed, and the core was cut into a cylindrical specimen with a diameter of 100 mm and a height of 150 mm (cut 10 mm up and down) (excluding fiber); a rutting plate specimen (300 mm × 300 mm × 50 mm) was formed (excluding fiber), 100 mm on both sides of the length and width were cut off, and the specimen was cut into a rectangular specimen (100 mm × 100 mm × 50 mm) along the height direction (excluding fiber).
[0046] (2) According to the fiber volume fraction of 0.3%, single-doped fibers of 3 mm, 6 mm, and 9 mm were used to prepare fiber-containing rotary compaction specimens with a diameter of 150 mm and a height of 170 mm. A cylindrical core sample (containing fiber) with a diameter of 100 mm and a height of 100 mm was drilled using a coring machine.
[0047] (3) There are two ways to obtain the skeleton feature image of the fiber-free asphalt mixture, which are as follows: ① or ②:
[0048] ① Photo acquisition: For the cored and cut specimen (without fiber, diameter 100 mm, height 150 mm), cut a section every 10 mm to obtain 15 sections of 10 mm high and 100 mm diameter specimens; cut and photograph the longitudinal surface (100 mm × 50 mm) of the rectangular specimen (100 mm × 100 mm × 50 mm, without fiber), cut a section every 10 mm to obtain 10 images of each layer of the longitudinal surface of the specimen;
[0049] ② CT scanning: An industrial CT machine was used to perform cross-sectional scanning on the specimen (100 mm in diameter, 150 mm in height, and excluding fibers) after coring and cutting. The specimen was scanned once every 10 mm. The specimen was scanned 15 times to obtain 15 CT images of each layer of the cross section of the specimen. The longitudinal section (100 mm × 50 mm) of the rectangular specimen (100 mm × 100 mm × 50 mm, excluding fibers) was scanned once every 10 mm to obtain 10 CT images of each layer of the longitudinal section of the specimen.
[0050] (4) Use MATLAB software to perform histogram equalization on the cross-sectional image, such as Figure 1 As shown in the figure, the grayscale distribution of the image is more balanced; then the median filter is used to reduce noise and make the image boundary clearer; finally, the threshold iteration algorithm is used to perform binarization processing to distinguish the gaps between skeletons and obtain the horizontal and vertical binary images of each layer respectively.
[0051] (5) The main axis length of the skeleton gap in the image is selected as the extracted characteristic parameter, and the image of the asphalt mixture skeleton binary image is calibrated using Image Pro Plus software. The skeleton gap to be measured is selected, and the main axis length of the skeleton gap to be measured is determined. Finally, the software built-in macro command is used for programming, the images are processed in batches, and the data is exported;
[0052] (6) Using statistics, the length data of the skeleton gaps are arranged in intervals, and the number of fibers in different intervals is counted. The distribution intervals are (0,3], (3,6), and [6,9]. According to the relative proportion of the number of distribution intervals, the relative proportion of fibers with different lengths is determined. The length of the fiber is slightly longer than the main axis length, so the mass ratio of fibers with different lengths is, m 3mm :m 6mm :m 9mm=Num(0,3]:Num(3,6):Num[6,9]; where Num is the number of skeleton gap main axis lengths in the corresponding interval; the above method is used to extract and count the skeleton gap main axis lengths of the transverse and longitudinal surfaces of the asphalt mixture, and the relative proportions of the combined length fibers determined according to the transverse surface X and the longitudinal surface Y are Xm and Y, respectively. 3mm :Xm 6mm :Xm 9mm and Ym 3mm :Ym 6mm :Ym 9mm .
[0053] (7) Perform CT scans on cylindrical core samples (100 mm in diameter and 100 mm in height) with single doping of 3 mm, 6 mm, and 9 mm fibers, respectively, and perform horizontal scans every 0.1 mm; import the scanned files into Mimics software, reconstruct the files using the built-in algorithm of Mimics, and extract the fibers;
[0054] According to the results extracted by Mimics software, the angle of single-length fiber (angle between fiber and bottom surface, range: 0°~90°) was calculated by built-in function of MATLAB software, and the proportion of single-length (3mm, 6mm, 9mm) fiber with angle between 0°~45° and 45°~90° with bottom transverse plane was counted. Fiber with angle between 0°~45° with bottom transverse plane was considered to be inclined to transverse plane, while fiber with angle between 45°~90° with bottom transverse plane was considered to be inclined to longitudinal plane, so the dispersion results (guidance coefficient ratio) of single-length (3mm, 6mm, 9mm) fiber were recorded as X 3mm (0°~45°), Y 3mm (45°~90°), X 6mm (0°~45°), Y 6mm (45°~90°), X 9mm (0°~45°), Y 9mm (45°~90°).
[0055] (8) Calculate the relative proportion of the final combined length fibers: M 3mm :M 6mm :M 9mm =[Xm 3mm *X 3mm (0°~45°)+Ym 3m *Y 3mm (45°~90°)]:[Xm 6mm *X 6mm (0°~45°)+Ym 6mm *Y 6mm (45°~90°)]:[Xm 9mm*X 9mm (0°~45°)+Ym 9mm *Y 9mm (45°~90°)], the result is 3mm:6mm:9mm=1:2:1.
[0056] For the asphalt middle surface layer of medium-grained asphalt concrete with 6cmAC-20 and 4.8% asphalt-stone ratio, the fiber gradation design method includes the following steps:
[0057] (1) According to the medium-grained asphalt concrete with 6 cm AC-20 and an asphalt-to-stone ratio of 4.8%, a rotary compaction specimen with a diameter of 150 mm and a height of 170 mm (excluding fiber) was formed, and the core was cut into a cylindrical specimen with a diameter of 100 mm and a height of 150 mm (cut 10 mm up and down) (excluding fiber); a rutting plate specimen (300 mm × 300 mm × 50 mm) was formed (excluding fiber), 100 mm on both sides of the length and width were cut off, and the specimen was cut into a rectangular specimen (100 mm × 100 mm × 50 mm) along the height direction (excluding fiber).
[0058] (2) According to the fiber volume fraction of 0.35%, single-doped fibers of 6 mm, 9 mm, and 12 mm were used to prepare fiber-containing rotary compaction specimens with a diameter of 150 mm and a height of 170 mm. A cylindrical core sample (containing fiber) with a diameter of 100 mm and a height of 100 mm was drilled using a coring machine.
[0059] (3) There are two ways to obtain the skeleton feature image of the fiber-free asphalt mixture, which are as follows: ① or ②:
[0060] ① Photo acquisition: For the cored and cut specimen (without fiber, diameter 100 mm, height 150 mm), cut a section every 10 mm to obtain 15 sections of 10 mm high and 100 mm diameter specimens; cut and photograph the longitudinal surface (100 mm × 50 mm) of the rectangular specimen (100 mm × 100 mm × 50 mm, without fiber), cut a section every 10 mm to obtain 10 images of each layer of the longitudinal surface of the specimen;
[0061] ② CT scanning: An industrial CT machine was used to perform cross-sectional scanning on the specimen (100 mm in diameter, 150 mm in height, and excluding fibers) after coring and cutting. The specimen was scanned once every 10 mm. The specimen was scanned 15 times to obtain 15 CT images of each layer of the cross section of the specimen. The longitudinal section (100 mm × 50 mm) of the rectangular specimen (100 mm × 100 mm × 50 mm, excluding fibers) was scanned once every 10 mm to obtain 10 CT images of each layer of the longitudinal section of the specimen.
[0062] (4) The cross-sectional images were processed with histogram equalization using MATLAB software to make the grayscale distribution of the image more balanced; then the images were subjected to median filtering for noise reduction to make the image boundaries clearer; finally, the images were binarized using a threshold iteration algorithm to distinguish between the skeletons and the gaps between them, and the horizontal and vertical binary images of each layer were obtained.
[0063] (5) The main axis length of the skeleton gap in the image is selected as the extracted characteristic parameter, and the image of the asphalt mixture skeleton binary image is calibrated using Image Pro Plus software. The skeleton gap to be measured is selected, and the main axis length of the skeleton gap to be measured is determined. Finally, the software built-in macro command is used for programming, the images are processed in batches, and the data is exported;
[0064] (6) Using statistics, the length data of the skeleton gaps are arranged in intervals, and the number of fibers in different intervals is counted. The distribution intervals are (3,6], (6,9), and [9,12]. According to the relative proportion of the number of distribution intervals, the relative proportion of fibers of different lengths is determined. The length of the fiber is slightly longer than the main axis length, so the mass ratio of fibers of different lengths is, m 6mm :m 9mm :m 12mm =Num[3,6):Num(6,9):Num[9,12]; where Num is the number of skeleton gap main axis lengths in the corresponding interval; using the above method, the skeleton gap main axis lengths of the transverse and longitudinal surfaces of the asphalt mixture are extracted and counted, and the relative proportions of the combined length fibers determined according to the transverse surface X and the longitudinal surface Y are Xm and Y, respectively. 6mm :Xm 9mm :Xm 12mm and Ym 6mm :Ym 9mm :Ym 12mm .
[0065] (7) The cylindrical core samples (diameter 100 mm, height 100 mm) with single doping of 6 mm, 9 mm and 12 mm fibers were CT scanned, and horizontal scans were performed every 0.1 mm. The scanned files were imported into Mimics software, and the files were reconstructed using the built-in algorithm of Mimics to extract the fibers.
[0066] According to the results extracted by Mimics software, the angle of single-length fiber (angle between fiber and bottom surface, range: 0°~90°) was calculated by built-in function of MATLAB software, and the proportion of single-length (6mm, 9mm and 12mm) fiber with angle between 0°~45° and 45°~90° to the bottom transverse plane was counted. Fiber with angle between 0°~45° to the bottom transverse plane was considered to be inclined to the transverse plane, while fiber with angle between 45°~90° to the bottom transverse plane was considered to be inclined to the longitudinal plane, so the dispersion results (guidance coefficient ratio) of single-length (6mm, 9mm and 12mm) fiber were recorded as X 6mm (0°~45°), Y 6mm (45°~90°), X 9mm (0°~45°), Y 9mm (45°~90°), X 12mm (0°~45°), Y 12mm (45°~90°).
[0067] (8) Calculate the relative proportion of the final combined length fibers: M 6mm :M 9mm :M 12mm =[Xm 6mm *X 6mm (0°~45°)+Ym 6mm *Y 6mm (45°~90°)]:[Xm 9mm *X 9mm (0°~45°)+Ym 9mm *Y 9mm (45°~90°)]:[Xm 12mm *X 12mm (0°~45°)+Ym 12mm *Y 12mm (45°~90°)], the result is 6mm:9mm:12mm=1:2:2.
[0068] For the coarse-grained asphalt concrete bottom layer with 8cm AC-25 and 4.3% asphalt-to-stone ratio, the fiber gradation design method includes the following steps:
[0069] (1) According to the coarse-grained asphalt concrete with 8 cm AC-25 and 4.3% asphalt-stone ratio, a rotary compaction specimen with a diameter of 150 mm and a height of 170 mm (without fiber) was formed, and the core was cut into a cylindrical specimen with a diameter of 100 mm and a height of 150 mm (cut 10 mm up and down) (without fiber); a rutting plate specimen (300 mm × 300 mm × 50 mm) was formed (without fiber), 100 mm on both sides of the length and width were cut off, and the specimen was cut into a rectangular specimen (100 mm × 100 mm × 50 mm) along the height direction (without fiber).
[0070] (2) According to the fiber volume fraction of 0.4%, single-doped fibers of 9 mm, 12 mm, and 15 mm were used to prepare fiber-containing rotary compaction specimens with a diameter of 150 mm and a height of 170 mm. A cylindrical core sample (containing fiber) with a diameter of 100 mm and a height of 100 mm was drilled using a coring machine.
[0071] (3) There are two ways to obtain the skeleton feature image of the fiber-free asphalt mixture, which are as follows: ① or ②:
[0072] ① Photo acquisition: For the cored and cut specimen (without fiber, diameter 100 mm, height 150 mm), cut a section every 10 mm to obtain 15 sections of 10 mm high and 100 mm diameter specimens; cut and photograph the longitudinal surface (100 mm × 50 mm) of the rectangular specimen (100 mm × 100 mm × 50 mm, without fiber), cut a section every 10 mm to obtain 10 images of each layer of the longitudinal surface of the specimen;
[0073] ② CT scanning: An industrial CT machine was used to perform cross-sectional scanning on the specimen (100 mm in diameter, 150 mm in height, and excluding fibers) after coring and cutting. The specimen was scanned once every 10 mm. The specimen was scanned 15 times to obtain 15 CT images of each layer of the cross section of the specimen. The longitudinal section (100 mm × 50 mm) of the rectangular specimen (100 mm × 100 mm × 50 mm, excluding fibers) was scanned once every 10 mm to obtain 10 CT images of each layer of the longitudinal section of the specimen.
[0074] (4) The cross-sectional images were processed with histogram equalization using MATLAB software to make the grayscale distribution of the image more balanced; then the images were subjected to median filtering for noise reduction to make the image boundaries clearer; finally, the images were binarized using a threshold iteration algorithm to distinguish between the skeletons and the gaps between them, and the horizontal and vertical binary images of each layer were obtained.
[0075] (5) The main axis length of the skeleton gap in the image is selected as the extracted characteristic parameter, and the image of the asphalt mixture skeleton binary image is calibrated using Image Pro Plus software. The skeleton gap to be measured is selected, and the main axis length of the skeleton gap to be measured is determined. Finally, the software built-in macro command is used for programming, the images are processed in batches, and the data is exported;
[0076] (6) Using statistics, the length data of the skeleton gaps are arranged in intervals, and the number of fibers in different intervals is counted. The distribution intervals are (6,9), [9,12], and (12,15]. According to the relative proportion of the number of distribution intervals, the relative proportion of fibers with different lengths is determined. The length of the fiber is slightly longer than the main axis length. Therefore, the mass ratio of fibers with different lengths is, m 9mm :m 12mm :m 15mm =Num[6,9):Num[9,12]:Num(12,15]; where Num is the number of skeleton gap main axis lengths in the corresponding interval; the above method is used to extract and count the skeleton gap main axis lengths of the transverse and longitudinal surfaces of the asphalt mixture, and the relative proportions of the combined length fibers determined according to the transverse surface X and the longitudinal surface Y are Xm and Y respectively. 9mm :Xm 12mm :Xm 15mm and Ym 9mm :Ym 12mm :Ym 15mm .
[0077] (7) Perform CT scans on cylindrical core samples (100 mm in diameter and 100 mm in height) of single-doped 9 mm, 12 mm, and 15 mm fibers, and perform horizontal scans every 0.1 mm; import the scanned files into Mimics software, reconstruct the files using the built-in algorithm of Mimics, and extract the fibers;
[0078] According to the results extracted by Mimics software, the angle of single-length fiber (angle between fiber and bottom surface, range: 0°~90°) was calculated by built-in function of MATLAB software, and the proportion of single-length (9mm, 12mm and 15mm) fiber with angle between 0°~45° and 45°~90° to the bottom transverse plane was counted. Fiber with angle between 0°~45° to the bottom transverse plane was considered to be inclined to the transverse plane, while fiber with angle between 45°~90° to the bottom transverse plane was considered to be inclined to the longitudinal plane, so the dispersion results (guidance coefficient ratio) of single-length (9mm, 12mm and 15mm) fibers were recorded as X 9mm (0°~45°), Y 9mm (45°~90°), X 12mm (0°~45°), Y 12mm (45°~90°), X 15mm (0°~45°), Y 15mm (45°~90°).
[0079] (8) Calculate the relative proportion of the final combined length fibers: M 9mm :M 12mm :M 15mm =[Xm9mm *X 9mm (0°~45°)+Ym 9mm *Y 9mm (45°~90°)]:[Xm 12mm *X 12mm (0°~45°)+Ym 12mm *Y 12mm (45°~90°)]:[Xm 15mm *X 15mm (0°~45°)+Ym 15mm *Y 15mm (45°~90°)], the result is 9mm:12mm:15mm=2:2:1.
[0080] Comparative Example 1
[0081] The asphalt pavement structure of Comparative Example 1 includes a 4cm SMA-13 asphalt concrete upper layer with an oil-stone ratio of 6.0%, a 6cm AC-20 medium-grained asphalt concrete asphalt middle layer with an oil-stone ratio of 4.8%, an 8cm AC-25 coarse-grained asphalt concrete asphalt lower layer with an oil-stone ratio of 4.3%, a 36cm cement-stabilized gravel base layer and an 18cm low-dose cement-stabilized gravel subbase layer with a cement dosage of 4%.
[0082] Comparative Example 2
[0083] In Comparative Example 2, a high modulus agent is added to each asphalt surface layer on the basis of Comparative Example 1, and the specific adding method and amount are the same as those in Example 1.
[0084] Comparative Example 3
[0085] In Comparative Example 3, basalt fiber is added to each asphalt surface layer on the basis of Comparative Example 1, and the specific adding method and amount are the same as those in Example 1.
[0086] Performance Testing
[0087] According to the thickness of the asphalt surface layer in Example 1 and Comparative Examples 1-3, a rutting plate specimen with a thickness of 18 cm was prepared, wherein the upper layer was 4 cm SMA-13, the middle layer was 6 cm AC-20, and the lower layer was 8 cm AC-25. The overall structural performance of the pavement of these four embodiments was tested by rutting test, low temperature bending test, and dynamic modulus test according to the specification, and the results are shown in Tables 2 to 4 below:
[0088] Table 2 Rutting test results of asphalt pavement structure of Example 1 and asphalt pavement structure of Comparative Examples 1-2
[0089]
[0090]
[0091] Table 3 Low temperature bending test results of the upper, middle and lower layers of Example 1, Comparative Example 2 and Comparative Example 3
[0092] Pavement structure layer Maximum bending strain at specimen failure (με) Example 1 SMA-13 2862.6 Example 1AC-20 2688.3 Example 1AC-25 2574.2 Comparative Example 2 SMA-13 2300.8 Comparative Example 2AC-20 2206.2 Comparative Example 2AC-25 2117.7 Comparative Example 3 SMA-13 2883 Comparative Example 3AC-20 2704.2 Comparative Example 3AC-25 2596.3
[0093] Table 4 Dynamic modulus test results of the upper, middle and lower layers of Example 1 and Comparative Example 2
[0094] Pavement structure layer 20℃10Hz dynamic modulus (MPa) Example 1 SMA-13 16892 Example 1AC-20 17932 Example 1AC-25 15692 Comparative Example 2 SMA-13 16408 Comparative Example 2AC-20 17397 Comparative Example 2AC-25 15149
[0095] As shown in Table 2, the present invention improves the overall anti-rutting performance of the pavement by compounding the high modulus agent with a gradient structure and the graded fiber with a gradient structure. Combining Tables 2 and 3, it can also make the low-temperature anti-cracking performance of the pavement structure basically close to the low-temperature anti-cracking performance of the fiber alone; it can make the dynamic modulus of the pavement basically close to the dynamic modulus of the high modulus agent alone. The overall dynamic stability of the pavement of the present invention is improved by 64.3%, the maximum failure strain of the SMA-13 upper layer is increased by 24.4%, the maximum failure strain of the AC-20 middle layer is increased by 21.9%, and the maximum failure strain of the AC-25 lower layer is increased by 21.6%.
[0096] That is, the asphalt pavement performance improvement method of the present invention can simultaneously improve the rutting resistance and cracking resistance of the asphalt pavement and achieve a balance between the two by compounding high modulus agents and graded fibers on different pavement layers and forming a gradient incorporation method.
Claims
1. A method for improving the performance of asphalt pavement by combining gradient fiber content with gradient high modulus agent content, characterized in that The steps include: (1) Providing an asphalt pavement structure including an asphalt upper layer, an asphalt middle layer, an asphalt lower layer, a base layer and a subbase layer; (2) Add 0.8-1.0% of high modulus agent and 0.3-0.4% of graded fiber to the asphalt mixture of the upper asphalt layer; add 0.8-1.0% of high modulus agent and 0.3-0.4% of graded fiber to the asphalt mixture of the middle asphalt layer; add 0.3-0.5% of high modulus agent and 0.3-0.4% of graded fiber to the asphalt mixture of the lower asphalt layer, so as to form a gradient graded fiber dosage and a gradient high modulus agent dosage.
2. The method for improving asphalt pavement performance by compounding gradient fiber dosage with gradient high modulus agent dosage according to claim 1, characterized in that: In step (2), the design ratio of the graded fibers is: M 3nmm :M 3(n-1)mm :┄┄:M 3mm =[Xm 3nmm *X 3nmm (0°~45°)+Ym 3nmm *Y 3nmm (45°~90°)]:[Xm 3(n-1)mm *X 3(n-1)mm (0°~45°)+Ym 3(n-1) *Y 3(n-1)mm (45°~90°)]:┄┄:[Xm 3mm *X 3mm (0°~45°)+Ym 3mm *Y 3mm (45°~90°)]; In the formula, * represents the multiplication sign; M 3nmm is the mass ratio of 3n mm fiber, n is a positive integer; Xm 3nmm is the mass ratio of fibers of different lengths in the transverse section; X 3nmm (0-45°) is the guide coefficient ratio of fibers of different lengths with an angle between 0° and 45° with the transverse section; Ym 3nmm Y is the mass ratio of fibers of different lengths in the longitudinal section; 3nmm (45°~90°) is the ratio of the guidance coefficients of fibers of different lengths whose angles with the longitudinal section are between 45° and 90°.
3. The method for improving asphalt pavement performance by compounding gradient fiber dosage with gradient high modulus agent dosage according to claim 2, characterized in that: The design method of the graded fiber comprises the following steps: (1) According to the gradation and asphalt-stone ratio of asphalt mixture, cylindrical specimens and rectangular specimens without fibers were prepared respectively; (2) According to the gradation, asphalt-stone ratio and fiber volume content of the asphalt mixture, 3n mm single fiber cylindrical specimens were prepared, where n is a positive integer; (3) respectively obtaining skeleton feature images of different horizontal layers of the cylindrical specimen and skeleton feature images of different vertical layers of the rectangular specimen in step (1), and respectively performing binary image processing on both, so as to distinguish the skeleton and the gap between the skeletons of the asphalt mixture, and obtain binary images of the horizontal and vertical surfaces; (4) Based on the binary images of the transverse and longitudinal surfaces, the skeleton gap features of the binary images of the asphalt mixture are extracted, and the length data of the skeleton gaps are arranged in intervals to count the number of different intervals [3n-3,3n) mm and determine the lengths of different Xm 3nmm and Ym 3nmm The relative mass ratio of the length fiber; where X represents the transverse section, Y represents the longitudinal section, n is a positive integer, and m is the mass; (5) Obtain cross-sectional images of cylindrical specimens with single fibers of different lengths in step (2) respectively, obtain dispersion effect extraction diagrams of single-length fibers in asphalt mixtures, calculate fiber angles, and calculate the guide coefficient ratios of single-length fibers with angles between 0° and 45° and 45° and 90° with the bottom cross-plane, which are defined as X 3nmm (0~45°), Y 3nmm (45°~90°), X represents the transverse section, and Y represents the longitudinal section; (6) Combine the different Xm in step (4) 3nmm and Ym 3nmm The relative proportion of the length fibers and the guide coefficient ratio of the single length fibers in step (5) determine the final design ratio of the length fibers based on the three-dimensional feature combination: M 3nmm :M 3(n-1)mm :┄┄:M 3mm =[Xm 3nmm *X 3nmm (0°~45°)+Ym 3nmm *Y 3nmm (45°~90°)]:[Xm 3(n-1)mm *X 3(n-1)mm (0°~45°)+Ym 3(n-1) *Y 3(n-1)mm (45°~90°)]:┄┄:[Xm 3mm *X 3mm (0°~45°)+Ym 3mm *Y 3mm (45°~90°)]; where M 3nmm is the mass ratio of 3n mm fiber.
4. The method for improving asphalt pavement performance by combining gradient fiber content with gradient high modulus agent content according to claim 3, characterized in that: In step (3), the binarization image processing is performed based on MATLAB software to distinguish the gaps between skeletons.
5. The method for improving asphalt pavement performance by combining gradient fiber content with gradient high modulus agent content according to claim 1, characterized in that: In step (4), the extracted feature parameter is the principal axis length of the skeleton gap in the binary image.
6. The method for improving asphalt pavement performance by combining gradient fiber dosage with gradient high modulus agent dosage according to claim 1, characterized in that: In step (4), the value of n is 1≦n≦4, and the corresponding distribution interval of the length data of the skeleton gap is (0,3), [3,6), [6,9), [9,12].
7. The method for improving asphalt pavement performance by combining gradient fiber content with gradient high modulus agent content according to claim 6, characterized in that: The relative proportions of the horizontal and vertical planes are determined as Xm 3mm :Xm 6mm :Xm 9mm :Xm 12mm and Ym 3mm :Ym 6mm :Ym 9mm :Ym 12mm Combined length fibers.
8. The method for improving asphalt pavement performance by combining gradient fiber content with gradient high modulus agent content according to claim 7, characterized in that: The design ratio of fiber length based on three-dimensional characteristics is: M 3mm :M 6mm :M 9mm :M 12mm =[Xm 3mm *X 3mm (0°~45°)+Ym 3m *Y 3mm (45°~90°)]:[Xm 6mm *X 6mm (0°~45°)+Ym 6mm *Y 6mm (45°~90°)]:[Xm 9mm *X 9mm (0°~45°)+Ym 9mm *Y 9mm (45°~90°)]:[Xm 12mm *X 12mm (0°~45°)+Ym 12mm *Y 12mm (45°~90°)]。